The importance of waiting - Sanders, Jarred; Biron, David (eLife, 2014)
Neural circuits that prevent a male C. elegans worm from copulating for several minutes after ejaculation have been identified.
Keywords: G-CaMP; acetylcholine; ejaculation; dopamine; male mating behaviour; glutamate